The Dark Artifices: Queen of Air and Darkness - Book 3 Book 3 - Clare, Cassandra (New York : Margaret K. McElderry Books, 2018)
While the Clave teeters on the brink of civil war, Julian and Emma take desperate measures to put their forbidden love aside and focus on saving the world of Shadowhunters before the parabatai curse destroys everyone.
"A shadowhunters novel."
Keywords: Demonology -- Juvenile fiction; Magic -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Supernatural -- Juvenile fiction; Los Angeles (California) -- Juvenile fiction; Paranormal -- Juvenile fiction; Fantasy -- Juvenile fiction